2008
DOI: 10.1002/ajmg.a.32550
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a patient with an interstitial 1q deletion [del(1)(q24.1q25.3)] and distinctive skeletal abnormalities

Abstract: Here we report on a patient with an interstitial deletion on the long(q) arm of chromosome 1 who presents with a unique constellation of anomalies including brachydactyly type E, Müllerian agenesis, growth hormone deficiency, as well as other abnormalities. We present the clinical details of this patient's presentation, the skeletal findings, and provide characterization of the deletion at the molecular level. We postulate that these skeletal anomalies are distinctive to 1q deletions involving the 1q24q25 regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 34 publications
5
25
0
Order By: Relevance
“…In contrast to the literature, only 2% of all were deletions in our study. Interstitial deletions in chromosomes 1 and 5 are rarely reported (23,24). To our knowledge, interstitial deletions of 5q13-q22 and 1q22-q25 chromosome regions in prenatal diagnosis were observed for first time in our study.…”
Section: Resultssupporting
confidence: 48%
“…In contrast to the literature, only 2% of all were deletions in our study. Interstitial deletions in chromosomes 1 and 5 are rarely reported (23,24). To our knowledge, interstitial deletions of 5q13-q22 and 1q22-q25 chromosome regions in prenatal diagnosis were observed for first time in our study.…”
Section: Resultssupporting
confidence: 48%
“…57 However, the mechanism by which the miR-17 $ 92 cluster regulates skeletal development has not yet been fully elucidated Further associations between miRNAs and human skeletal development have been suggested from reports on patients with deletions or a translocation within chromosome 1q24 resulting in various skeletal abnormalities. [59][60][61][62][63][64] Recently, Ashraf et al reported two additional patients with microdeletions in 1q24q25 that display similar skeletal abnormalities as reported previously (i.e., short stature, brachydactyly, and facial dysmorphism). 65 The deletion mutation in one of these patients narrowed down the critical region causing these skeletal defects to that encoding dynamin-3 (DNM3) and two miRNAs located within intron 14 of this gene (miR-199a and miR-214).…”
Section: Mirnas Regulating Skeletal Development and Homeostasis-evidesupporting
confidence: 53%
“…LHX4 (LIM homeobox gene 4) and CENPL (centromeric protein L) were suggested to be the primary candidate genes for growth retardation in the 1q25-q32 region. Initially, several studies indicated that growth retardation was likely attributed to the low serum GH levels resulting from heterozygous deletion of LHX4 in patients [6-8]. Heterozygous mutations of LHX4 can lead to abnormalities of pituitary and cerebellum, the deficiency of growth hormone, and then growth retardation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Mice with null ASTN1 showed smaller sizes of cerebella, poorer balance and coordination, reduction in migration rates [17]. Of the eleven postnatal deletion cases harboring ASTN1 [2,3,6-8,10], six displayed brain structure malformations [2,3,7,10], four were normal by MRI analysis [8,10], and the remaining one is unknown. We concluded that heterozygous ASTN1 deletion could be an important cause of the mental retardation in 1q25-32 deletion patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation